Study The Impact Of Disturbance Fulfillment Sexuality Needs After Heart Attack On Acute Myocardial Infarction In Men Patients On Cardiac Poly Clinic Dr. Iskak Hospital Tulungagung - Eko Arik Susmiatin; Rika Yolanda Sari (Akademi Keperawatan Dharma Husada Kediri, 2017)
Basic human needs is the most basic physiological needs, including sexual needs in it. Sexual fulfillment in the husband-wife not everything can be done well because of several factors, one of them due to heart disease (acute myocardial infarction). AMI patients are usually the same as the other pair, really wants her sexual needs fulfilled, but they are afraid to do it because they fear an attack recurrence. Impacts that could result from unfulfilled sexual needs including couples will quickly get angry or suspicious, unhappy, cynical, psychological relation between husband and wife is getting worse, decreasing the frequency of coitus, having psychosomatic illness. The research objective was to determine the impact of sexual fulfillment disorders after cardiac arrest in patients with acute myocardial infarction (AMI) in men Poly Clinic Heart Dr.Iskak Hospital Tulungagung. The study design used is descriptive design. Population of outpatients each month reaches 5-8, the sample used 8 people, taken with accidental sampling technique. Results of research obtained from all respondents stating no interference effects occur sexuality needs. This is due to the coping meccanism of the respondent and couple, and mutual understanding, and the support the family, so there is no impact of interference sexuality needs.Expected partner (wife) will understand situation the disturbed husband after Acute Myocardial Infarction attack occurred, and should be more active respondents also asked the doctor when the control, so the impact was not to happen. And for nurses, should provide health education about sexuality needs of post-heart attack.